Alcohol Use and Mental Health Conditions Among Black College Males: Do Those Attending Postsecondary Minority Institutions Fare Better Than Those at Primarily White Institutions?. (July 2017) - Barry, Adam E.; Jackson, Zachary; Watkins, Daphne C.; Goodwill, Janelle R.; Hunte, Haslyn E.R.
While there is a sizeable body of research examining the association between alcohol use and mental health conditions among college students, there are sparse investigations specifically focusing on these associations among Black college students. This is concerning given Black college students face different stressors compared with their non-Black peers. Black males appear especially at risk, exhibiting increased susceptibility to mental health issues and drinking in greater quantities and more frequently than Black females. This investigation examined the association between alcohol consumption and mental health conditions among Black men attending institutions of higher education in the United States and sought to determine differences between Black men attending predominantly White institutions (PWIs) compared with those attending postsecondary minority institutions. Final sample included 416 Black men, 323 of which attended a PWI. Data were from the National College Health Assessment. Black men attending a PWI reported significantly greater levels of alcohol consumption and significantly more mental health conditions. Attendance at a minority-serving institution was associated with fewer mental health conditions among Black men. Future studies should seek to replicate these findings and conduct culturally sensitive and gender-specific research examining why Black men at PWIs report greater alcohol consumption and more mental health conditions than their peers attending postsecondary minority institutions.